2015
DOI: 10.1038/nature16071
|View full text |Cite
|
Sign up to set email alerts
|

Brain tumour cells interconnect to a functional and resistant network

Abstract: Astrocytic brain tumours, including glioblastomas, are incurable neoplasms characterized by diffusely infiltrative growth. Here we show that many tumour cells in astrocytomas extend ultra-long membrane protrusions, and use these distinct tumour microtubes as routes for brain invasion, proliferation, and to interconnect over long distances. The resulting network allows multicellular communication through microtube-associated gap junctions. When damage to the network occurred, tumour microtubes were used for rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

50
1,115
2
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 879 publications
(1,223 citation statements)
references
References 61 publications
50
1,115
2
7
Order By: Relevance
“…33 This could be of relevance for analysis of stem cell populations that reside in defined anatomical spaces (e.g., as defined by hypoxia or vascular proximity), thereby enabling evaluation of their functional properties in their anatomical context. 34,35 Taken together, we have demonstrated that optical barcoding is a powerful tool that allows identification, quantification, tracking, and sorting of clonal subpopulations, as well as their functional assessment in vitro and in vivo. Complex heterogeneous systems are the result of the expansion of specific subpopulations driven by endogenous growth advantages, signaling networks, and selective pressure of the microenvironment.…”
Section: Discussionmentioning
confidence: 86%
“…33 This could be of relevance for analysis of stem cell populations that reside in defined anatomical spaces (e.g., as defined by hypoxia or vascular proximity), thereby enabling evaluation of their functional properties in their anatomical context. 34,35 Taken together, we have demonstrated that optical barcoding is a powerful tool that allows identification, quantification, tracking, and sorting of clonal subpopulations, as well as their functional assessment in vitro and in vivo. Complex heterogeneous systems are the result of the expansion of specific subpopulations driven by endogenous growth advantages, signaling networks, and selective pressure of the microenvironment.…”
Section: Discussionmentioning
confidence: 86%
“…Invading tumor cells escape at the periphery of the tumor mass and diffusely infiltrate the normal brain parenchyma (47). Deeply infiltrated tumor cells are more likely to escape surgery, and we do not know whether infiltration is a property of a more resilient cell population that initiates and drives tumor recurrence.…”
Section: Complexity Of Tumor Heterogeneity In Gbmmentioning
confidence: 99%
“…Heterogeneity at the cellular level adds another layer of complexity ( Figure 1C). Astoundingly, although these observations hint at each tumor cell being unique, tumor cells can be connected in a network that responds to a therapeutic insult in a coordinated fashion (47). Regional heterogeneity in molecular properties of tumor cells is thus governed by local variation in environmental selection forces.…”
Section: The Process Of Tumor Recurrence In Gbmmentioning
confidence: 99%
“…1E) (Scarpa et al 2015). Examples are the migration of neural crest cells in developing embryos, neuronal/astrocyte networks (Scarpa et al 2015), glioma cells retaining filamentous cell -cell interactions while moving through complex brain parenchyma (Osswald et al 2015), and mesenchymal tumor cells moving through confining tissue (Ilina et al 2011;Haeger et al 2014). Collectively, moving loose networks are mediated by complex morphological junctions mediated by N-cadherin for cell-cell adhesion and additional receptors mediating repulsive signals, including Ephrin/Eph receptors (Theveneau and Mayor 2011).…”
Section: Cell-cell Adhesion States and Dynamicsmentioning
confidence: 99%